Comparison of milk yield, selected reproductive performance and health problems between a dairy farm on concrete and another on rubber mat flooring - Mohamad Tahir, Nur Diyana (2015)
The objective of this study was to compare the milk yield, reproductive performance and health of dairy cows between a farm with rubber mat flooring (RF) and a farm with concrete flooring (CF). Two ‘Ladang Angkat’ Universiti Putra Malaysia farms were selected: RF farm is located in Lenggeng, Negeri Sembilan and the CF farm is in Kajang, Selangor. Thirty lactating cows from each farm were selected and the milk yield was recorded for nine days consecutively. Farmers were interviewed for farm information on reproductive performance and health problems. Clinical mastitis was assessed based on udder and milk abnormalities and lameness by locomotion score. The results revealed that the average daily milk yield of cows from RF farm was 18.01 litres (standard deviation, SD=1.5) and cows from CF farm was 8.3 litres (SD=1.4), of which the difference average milk yield was statistically significant (t-value=77.8, df=538, p<0.05). The selected clinical reproductive problems for both farms were similar (p>0.05). Farm on RF had significantly lower prevalence of clinical mastitis (Fisher’s exact test, p<0.05) and lameness (χ2=18.4, p<0.05), compared to CF farm. This study generally suggests that dairy cows kept on RF farm may perform better compared to cows from CF farm.